Organizational Communication Study: Organizational Control Theory Implementation by HMI Purwokerto Branch in the Omnibus Law Demonstration - Pundra Rengga Andhita; Ade Tuti Turistiati; Muhammad Jamiluddin Nur (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2021)
This study aims to examine the organizational communication control strategy carried out by the Purwokerto Branch of the Islamic Student Association (HMI) to demonstrate the Ratification of the Job Creation Bill (Omnibus Law). The method used is descriptive qualitative using organizational control theory as a theoretical framework. The results showed that the involvement of the Purwokerto Branch of HMI in the Omnibus Law demonstration was a critical intellectual movement that arranged forward a constitutional approach. The simple control aspect is implemented through a three-layer communication mechanism. The solidarity of members towards the three layers of communication constructs communication conduct harmoniously. HMI uses two technical tools for technical control, specifically communication aids and internal identification tools as non-verbal symbols of the organization. There are strict controls to identify members in the demonstration through the symbol. Regarding bureaucracy, this organization prioritizes communication with local authorities regarding the fulfillment of formal rules before holding a demonstration. In addition, organizational procedures are also carefully considered, especially regarding consolidating the organization’s internal communications. Conservative control is implemented by strengthening interpersonal communication with active members or alumni networks spread across various professions. The organizational communication control strategy of the HMI Purwokerto Branch focuses on the harmonization of demonstrations that prioritize aspirational and implementation communication by emphasizing a constitutional approach.